Structural Adaptation of the Excitation–Contraction Coupling Apparatus in Calsequestrin1-Null Mice during Postnatal Development - Stefania Murzilli; Matteo Serano; Laura Pietrangelo; Feliciano Protasi; Cecilia Paolini (Biology, 2023)
The precise arrangement and peculiar interaction of transverse tubule (T-tubule) and sarcoplasmic reticulum (SR) membranes efficiently guarantee adequate contractile properties of skeletal muscle fibers. Fast muscle fibers from mice lacking calsequestrin 1 (CASQ1) are characterized by the profound ultrastructural remodeling of T-tubule/SR junctions. This study investigates the role of CASQ1, an essential component of calcium release units (CRUs), in the postnatal development of muscle fibers. By using CASQ1-knockout mice, we examined the maturation of CRUs and the involvement of different junctional proteins in the juxtaposition of the membrane system. Our morphological investigation of both wild-type (WT) and CASQ1-null extensor digitorum longus (EDL) fibers, from 1 week to 4 months of age, yielded noteworthy findings. Firstly, we observed that the absence of CASQ1 hindered the full maturation of CRUs, despite the correct localization of key junctional components (ryanodine receptor, dihydropyridine receptor, and triadin) to the junctional SR in adult animals. Furthermore, analysis of protein expression profiles related to T-tubule biogenesis and organization (junctophilin 1, amphiphysin 2, caveolin 3, and mitsugumin 29) demonstrated delayed progression in their expression during postnatal development in the absence of CASQ1, suggesting the impaired maturation of CRUs. The absence of CASQ1 directly impacts the proper assembly of CRUs during development and influences the expression and coordination of other proteins involved in T-tubule biogenesis and organization.